Photocatalysis and biodegradation coupled catalytic material as well as preparation method and application thereof
By loading the sodium fluoride-based TiO2/reduced graphene oxide composite on a polyurethane sponge and hanging a biofilm, a photocatalytic and biodegradable catalytic material is formed, which solves the problems of high energy consumption and difficulty in regulation of antibiotic wastewater treatment in the prior art, and achieves efficient degradation of ciprofloxacin wastewater.
Patent Information
- Application Number
- CN202411963356.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art has problems of high energy consumption and difficulty in regulating antibiotic wastewater, and the degradation rate of photocatalytic materials and the loading rate of catalysts need to be improved.
By loading the sodium fluoride-based TiO2/reduced graphene oxide composite on a three-dimensional porous polyurethane sponge and carrying a bio-mounted film, it forms a photocatalytic and biodegradable catalytic material, which is applied to the treatment of ciprofloxacin wastewater.
It realizes efficient degradation of ciprofloxacin wastewater, improves the degradation rate of photocatalytic materials and the loading rate of catalysts, reduces energy consumption and simplifies the regulation process.
Smart Images

Figure CN119897162A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and specifically relates to a photocatalytic and biodegradation coupled catalytic material and a preparation method and application thereof. Background Art
[0002] Ciprofloxacin (Ciprofloxacin, CIP) is a class of artificially synthesized broad-spectrum antibacterial drugs, which are widely used in many fields such as human medicine, animal disease treatment and animal husbandry. Since it cannot be completely absorbed and metabolized after entering the human body or animal body, 30-90% will be directly excreted into the body through urine or feces in the form of parent compounds, and finally enter various environmental media through migration and transformation. Among them, the water environment is one of the main destinations of antibiotics. The difficult-to-degrade CIP in the water body will have potential adverse effects on non-target organisms and even aquatic ecosystems, and the microbial resistance caused by antibiotics is difficult to eliminate due to its persistent existence and gene horizontal transfer. At present, the treatment of antibiotic wastewater is generally carried out by means of indirect coupling of advanced oxidation process and biodegradation process, which has problems such as high energy consumption and difficult regulation. Therefore, the development of new technologies for efficient removal of antibiotics is of great significance to ensure the quality of the water environment.
[0003] As an emerging wastewater treatment technology, intimately coupled of photocatalysis and biodegradation (ICPB) breaks the traditional concept that photocatalytic reaction and biodegradation must be carried out separately in different reactors. Under the excitation of ultraviolet light or visible light, the photocatalyst on the outer surface of the carrier will produce highly oxidizing active species, degrading organic matter into bioavailable intermediates. The microorganisms inside the carrier further biodegrade the photocatalytic intermediates while removing the parent compounds, thereby achieving a high degree of degradation and mineralization of pollutants. This technology can make up for the defects of single processes of photocatalytic oxidation or biodegradation, and avoid the problem of insufficient degradation or excessive oxidation of original pollutants caused by improper control of photocatalytic degradation. It has good application prospects in the field of wastewater treatment.
[0004] A highly efficient photocatalytic catalyst is an important prerequisite for the successful construction of an ICPB system. Chinese patent document CN117902727A discloses a photocatalytic-biodegradable coupled wastewater treatment composite material, including a photocatalytic material and a biodegradable material. The photocatalytic material is Ag3PO4 / Bi3Ti4O 12The biodegradable material is a product obtained by soaking the carrier in excess sludge and forming biofilm in nitrate culture medium in turn. After long-term irradiation with visible light for 12 hours, the degradation efficiency of sulfamethoxazole is only 87.5%. The Chinese patent document CN110975932A discloses a method for preparing a photocatalytic carrier combining a nano-scale inorganic catalyst powder with an organic high molecular polymer surface. TiO2 is loaded on a polyurethane sponge with the help of a silane coupling agent, with a maximum loading of about 360 mg / g and a loading rate of about 36%. Therefore, the degradation rate of the photocatalytic material and the loading rate of the catalyst need to be further improved to enhance the wastewater treatment capacity of the ICPB system. Summary of the invention
[0005] The purpose of the present invention is to provide a photocatalytic and biodegradation coupling catalytic material in view of the above technical problems. A sodium fluoride-based TiO2 / reduced graphene oxide composite material is loaded on a three-dimensional porous polyurethane sponge through a polymer adhesive, and biofilm is formed on this basis. The obtained ICPB system is applied to treat ciprofloxacin wastewater and has a good degradation efficiency for antibiotics.
[0006] The photocatalytic and biodegradation coupled catalytic material in the technical solution of the present invention comprises a polyurethane sponge and a sodium fluoride-based TiO2 / reduced graphene oxide composite material loaded on the polyurethane sponge, wherein the polyurethane sponge and the sodium fluoride-based TiO2 / reduced graphene oxide composite material are connected by a thermoplastic resin adhesive.
[0007] Reduced graphene oxide (rGO) can convert the photogenerated electrons (e - ) can be quickly transferred, promoting its separation from the holes; on the other hand, its large specific surface area can provide more active sites for the catalytic reaction and promote the progress of the catalytic reaction.
[0008] Furthermore, the mass of the sodium fluoride-based TiO2 / reduced graphene oxide composite material is 20 to 80% of the mass of the polyurethane sponge.
[0009] Furthermore, a method for preparing a sodium fluoride-based TiO2 / reduced graphene oxide composite material is provided, wherein a sodium fluoride dispersion is added dropwise to a tetrabutyl titanate dispersion for mixed reaction, the product is aged, dried, and ground, and then calcined at high temperature to obtain a TiO2 material, and then the TiO2 material, graphene oxide, and sodium fluoride are added to the mixed solution for hydrothermal reaction, and finally washed, dried, and ground. The obtained sodium fluoride-based TiO2 / reduced graphene oxide composite material is recorded as NaF-TiO2 / rGO.
[0010] Adding sodium fluoride during the hydrothermal reaction is beneficial to reducing the surface energy of the
[001] crystal plane and maintaining its original
[001] crystal plane. In addition, the O element in the sodium fluoride-based-TiO2 (NaF-TiO2) lattice can be partially replaced by the F element, which reduces the band gap of NaF-TiO2 and has stronger absorption capacity in the visible light region.
[0011] Preferably, the solvent of the tetrabutyl titanate dispersion is ethanol with a volume fraction of 40-60%; the solvent of the sodium fluoride dispersion is a mixture of ethanol and water with a volume ratio of 50-80% and a mass concentration of sodium fluoride of 0.05-0.20 g / mL.
[0012] Preferably, the aging temperature is 20-30°C for 10-20 hours; and the drying temperature is 60-100°C.
[0013] Furthermore, the high temperature calcination temperature is 500-800° C., and the time is 1-5 hours.
[0014] Preferably, graphene oxide is prepared by a modified Hummers method.
[0015] Furthermore, the mass percentages of TiO2 material, graphene oxide and sodium fluoride are 35-90%, 0.1-0.5% and 10-65% respectively.
[0016] Preferably, the mixed solution is a mixture of ethanol and water, wherein the volume ratio of ethanol to water is 10-30%.
[0017] Furthermore, the mass concentration of TiO2 material in the mixed solution is 0.01-0.05 g / mL.
[0018] Furthermore, the temperature of the hydrothermal reaction is 80 to 160° C., preferably 80 to 100° C., and the time is 5 to 10 hours.
[0019] Furthermore, the thermoplastic resin adhesive is soluble in alcohol compounds, including but not limited to one or more of polyvinyl acetate, polyvinyl acetal, and ethylene-vinyl acetate copolymer resin. Thermoplastic resin adhesives soluble in alcohol compounds are relatively stable in the water phase and have excellent aging resistance, and can maintain their adhesion and impact resistance with the photocatalytic and biodegradable coupling catalytic material for a long time.
[0020] The present invention also provides a method for preparing the above-mentioned photocatalytic and biodegradable coupled catalytic material, comprising the following steps: adding an alcohol compound to a thermoplastic resin adhesive, heating and stirring until dissolved, adding a polyurethane sponge and stirring evenly, then adding a suspension of a sodium fluoride-based TiO2 / reduced graphene oxide composite material and mixing evenly, drying and washing, to obtain a polyurethane sponge loaded with the sodium fluoride-based TiO2 / reduced graphene oxide composite material.
[0021] Preferably, the alcohol compound is any one of ethanol and acetone.
[0022] Furthermore, the volume of the thermoplastic resin adhesive is 0.8-2.0% of the volume of the alcohol compound.
[0023] Preferably, the temperature for heating and stirring is 80 to 150°C.
[0024] Furthermore, the mass of the polyurethane sponge relative to the alcohol compound is 0.1-1.0 g / 100 mL.
[0025] Preferably, the solvent used for the suspension of the sodium fluoride-based TiO2 / reduced graphene oxide composite material is ethanol, wherein the concentration of the sodium fluoride-based TiO2 / reduced graphene oxide composite material is 2.0-8.0 mg / mL.
[0026] Preferably, the drying is carried out in a forced air drying oven at 60-100° C. until the liquid is completely evaporated.
[0027] The present invention also provides application of the above-mentioned photocatalytic and biodegradation coupled catalytic material in treating ciprofloxacin wastewater.
[0028] Furthermore, when the above-mentioned photocatalytic and biodegradable coupled catalytic material is used in treating ciprofloxacin wastewater, the photocatalytic and biodegradable coupled catalytic material is immersed in activated sludge for exposure, and then transferred to an SBR reactor for operation. The obtained photocatalytic and biodegradable coupled catalytic material is then taken out and placed in an SBR reactor without activated sludge for operation.
[0029] Preferably, the photocatalytic and biodegradable coupled catalytic material is immersed in activated sludge and exposed for 20 to 30 hours, then transferred to an SBR reactor and operated for 10 to 12 days, and then the obtained photocatalytic and biodegradable coupled catalytic material is taken out and placed in an SBR reactor without activated sludge and operated for 60 to 80 days.
[0030] Furthermore, when operating in an SBR reactor without activated sludge, the stepwise addition of ciprofloxacin to the experimental water could form an antibiotic tolerance process.
[0031] Furthermore, ciprofloxacin was added stepwise into the experimental water according to 0.0 mg / L for 0-10 days, 0.1-0.2 mg / L for 11-25 days, 0.9-1.1 mg / L for 26-40 days, 9.0-11.0 mg / L for 41-55 days, and 18.0-21.0 mg / L for 56-70 days.
[0032] Furthermore, the water used when the photocatalytic and biodegradation coupled catalytic material is operated in the SBR reactor is artificially prepared simulated urban sewage.
[0033] Furthermore, the photocatalytic and biodegradable coupling catalytic material is operated in the SBR reactor at a speed of 0.1 to 0.5 m 3 Oxygen is supplied to the reactor at a rate of / h.
[0034] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0035] (1) A sodium fluoride-based TiO2 / reduced graphene oxide composite material is loaded on a three-dimensional porous polyurethane sponge through a thermoplastic resin adhesive soluble in alcohol compounds to obtain a photocatalytic and biodegradable coupled catalytic material;
[0036] (2) Based on the obtained photocatalytic and biodegradation coupled catalytic material, biofilm formation was carried out, and the obtained ICPB system was used to treat ciprofloxacin wastewater, and had a good degradation efficiency for antibiotics;
[0037] (3) Reduced graphene oxide (rGO) can convert the photogenerated electrons (e) generated by sodium fluoride-based TiO2 into - ) quickly transfers, promoting its separation from the hole; on the other hand, its large specific surface area can provide more active sites for the catalytic reaction, promoting the catalytic reaction;
[0038] (4) Thermoplastic resin adhesives that are soluble in alcohol compounds are relatively stable in the water phase and have excellent aging resistance. They can maintain their adhesion and impact resistance with the photocatalytic and biodegradable coupling catalytic materials for a long time, ensuring the degradation efficiency of the ICPB system;
[0039] (5) When the obtained photocatalytic and biodegradation coupled catalytic material is used to treat ciprofloxacin wastewater, ciprofloxacin is added step by step to form an antibiotic tolerance process. The obtained ICPB system has a long operating time and can maintain long-term catalytic degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the SEM image of the ICPB system obtained in Application Example 1;
[0041] Figure 2This is a SEM image of a single biofilm obtained in Comparative Example 1; Figure 3 The photocatalytic activity diagram of the photocatalytic and biodegradation coupled catalytic materials obtained in Example 1 and Examples 3-5;
[0042] Figure 4 The photocatalytic activity diagram of the photocatalytic and biodegradation coupled catalytic materials obtained in Example 1 and Examples 6-8;
[0043] Figure 5 The photocatalytic activity diagram of the photocatalytic and biodegradation coupled catalytic materials obtained in Example 1 and Examples 9-12;
[0044] Figure 6 The photocatalytic activity diagram of the photocatalytic and biodegradation coupled catalytic materials obtained in Example 1 and Examples 13-15;
[0045] Figure 7 This is a photocatalytic activity diagram of the ICPB biofilm prepared using the photocatalytic and biodegradation coupled catalytic material obtained in Example 1. DETAILED DESCRIPTION
[0046] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0047] In the present invention, graphene oxide is prepared by an improved Hummers method, comprising the following steps:
[0048] (1) Weigh 23 mL of concentrated sulfuric acid (mass concentration of 66 wt%) and place it in a conical flask, cool it to 3°C in an ice bath, add 1 g of graphite powder and 0.5 g of sodium nitrate, continue stirring for 1 hour, then slowly add 4.5 g of potassium permanganate, control the temperature to no more than 20°C, and react for 2 hours;
[0049] (2) Place the conical flask in a 38°C constant temperature water bath, stir and react for 2 h, slowly add 46 mL of deionized water, and obtain a mixed solution after the reaction. Place it in a 95°C constant temperature water bath for 30 min, immediately add 70 mL of deionized water to terminate the reaction, and finally add 15 mL of hydrogen peroxide (30 Vol%), react for 15 min, then add 40 mL of hydrochloric acid solution (10 Vol%), wash by low-speed centrifugation, ultrasonically peel for 40 min, and dry after centrifugation.
[0050] Example 1
[0051] The method for preparing the photocatalytic and biodegradable coupled catalytic material of this embodiment comprises the following steps:
[0052] (1) 5 mL of tetrabutyl titanate was ultrasonically dispersed in 10 mL of ethanol to obtain a tetrabutyl titanate dispersion, 0.8 g of sodium fluoride was ultrasonically dispersed in 10 mL of a mixture of ethanol and water (the volume fraction of ethanol was 60%) to obtain a sodium fluoride dispersion, the sodium fluoride dispersion was dropwise added to the tetrabutyl titanate dispersion and ultrasonically mixed for 40 min, the obtained product was aged at 25° C. for 12 h and then dried at 80° C., fully ground and calcined at 600° C. for 2 h to obtain a TiO2 material with synergistic crystal faces;
[0053] (2) 1.5 g of the obtained TiO2 material, 0.006 g of graphene oxide and 0.64 g of sodium fluoride were added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol was 20%), and then ultrasonically mixed and hydrothermally reacted at 100 °C for 10 h. Finally, the mixture was washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, which was recorded as NaF-TiO2 / rGO.
[0054] (3) 0.08 g of NaF-TiO2 / rGO was ultrasonically dispersed in 40 mL of ethanol to obtain an ethanol suspension of NaF-TiO2 / rGO; then 100 mL of ethanol was added to 1.2 mL of polyvinyl butyral, heated at 100 °C and stirred until dissolved, then 0.4 g of polyurethane sponge was added and stirred evenly, and then the ethanol suspension of NaF-TiO2 / rGO was added, and after ultrasonic mixing, the mixture was dried in a forced air drying oven at 80 °C until the liquid was completely evaporated, and then ultrasonically cleaned in distilled water again to remove the NaF-TiO2 / rGO that was not firmly loaded on the surface of the polyurethane sponge.
[0055] Example 2
[0056] The method for preparing the photocatalytic and biodegradable coupled catalytic material of this embodiment comprises the following steps:
[0057] (1) 5 mL of tetrabutyl titanate was ultrasonically dispersed in 10 mL of ethanol to obtain a tetrabutyl titanate dispersion, 0.8 g of sodium fluoride was ultrasonically dispersed in 8 mL of a mixture of ethanol and water (the volume fraction of ethanol was 60%) to obtain a sodium fluoride dispersion, the sodium fluoride dispersion was dropwise added to the tetrabutyl titanate dispersion and ultrasonically mixed for 40 min, the obtained product was aged at 25° C. for 12 h and then dried at 80° C., fully ground and calcined at 700° C. for 2 h to obtain a TiO2 material with synergistic crystal faces;
[0058] (2) 1.5 g of the obtained TiO2 material, 0.006 g of graphene oxide and 0.64 g of sodium fluoride were added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol was 20%), and then ultrasonically mixed and hydrothermally reacted at 100 °C for 10 h. Finally, the mixture was washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, which was recorded as NaF-TiO2 / rGO.
[0059] (3) 0.08 g of NaF-TiO2 / rGO was ultrasonically dispersed in 30 mL of ethanol to obtain an ethanol suspension of NaF-TiO2 / rGO; then 100 mL of ethanol was added to 1.5 mL of polyvinyl butyral, heated at 100 °C and stirred until dissolved, then 0.4 g of polyurethane sponge was added and stirred evenly, and then the ethanol suspension of NaF-TiO2 / rGO was added, and after ultrasonic mixing, the mixture was dried in a forced air drying oven at 80 °C until the liquid was completely evaporated, and then ultrasonically cleaned in distilled water to remove the NaF-TiO2 / rGO that was not firmly loaded on the surface of the polyurethane sponge.
[0060] Example 3
[0061] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.004 g of graphene oxide and 0.64 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 100° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, denoted as NaF-TiO2 / rGO; the mass percentages of TiO2 material, graphene oxide and sodium fluoride are 69.8%, 0.2% and 30%, respectively.
[0062] Example 4
[0063] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.002 g of graphene oxide and 0.64 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 100° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, denoted as NaF-TiO2 / rGO; the mass percentages of TiO2 material, graphene oxide and sodium fluoride are 69.9%, 0.1% and 30%, respectively.
[0064] Example 5
[0065] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.009 g of graphene oxide and 0.64 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 100° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, denoted as NaF-TiO2 / rGO; the mass percentages of TiO2 material, graphene oxide and sodium fluoride are 69.6%, 0.4% and 30%, respectively.
[0066] Example 6
[0067] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.008 g of graphene oxide and 1.23 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 100° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, denoted as NaF-TiO2 / rGO; the mass percentages of TiO2 material, graphene oxide and sodium fluoride are 54.7%, 0.3% and 45%, respectively.
[0068] Example 7
[0069] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.011 g of graphene oxide and 2.27 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 100° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, denoted as NaF-TiO2 / rGO; the mass percentages of TiO2 material, graphene oxide and sodium fluoride are 39.7%, 0.3% and 60%, respectively.
[0070] Example 8
[0071] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.005 g of graphene oxide and 0.26 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 100° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, denoted as NaF-TiO2 / rGO; the mass percentages of TiO2 material, graphene oxide and sodium fluoride are 84.7%, 0.3% and 15%, respectively.
[0072] Example 9
[0073] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.006 g of graphene oxide and 0.64 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 120° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, recorded as NaF-TiO2 / rGO.
[0074] Example 10
[0075] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.006 g of graphene oxide and 0.64 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 140° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, recorded as NaF-TiO2 / rGO.
[0076] Embodiment 11
[0077] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.006 g of graphene oxide and 0.64 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 160° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, recorded as NaF-TiO2 / rGO.
[0078] Example 12
[0079] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of the obtained TiO2 material, 0.006 g of graphene oxide and 0.64 g of sodium fluoride are added to a mixture of 50 mL of ethanol and water (the mass fraction of ethanol is 20%), ultrasonically mixed and hydrothermally reacted at 80° C. for 10 h, and finally washed with ultrapure water, dried and ground to obtain a sodium fluoride-based TiO2 / graphene oxide composite material, recorded as NaF-TiO2 / rGO.
[0080] Example 13
[0081] The difference between this embodiment and embodiment 1 is that in step (3), 0.16 g of NaF-TiO2 / rGO is ultrasonically dispersed in 40 mL of ethanol to obtain an ethanol suspension of NaF-TiO2 / rGO; then, 100 mL of ethanol is added to 1.2 mL of polyvinyl butyral, and the mixture is heated at 100° C. and stirred until dissolved, and then 0.4 g of polyurethane sponge is added and stirred evenly, and then the ethanol suspension of NaF-TiO2 / rGO is added, and after ultrasonic mixing, the mixture is dried in a blast drying oven at 80° C. until the liquid is completely evaporated, and then ultrasonically cleaned in distilled water to remove the NaF-TiO2 / rGO that is not firmly loaded on the surface of the polyurethane sponge; the mass of NaF-TiO2 / rGO is 40% of the mass of the polyurethane sponge.
[0082] Embodiment 14
[0083] The difference between this embodiment and embodiment 1 is that in step (3), 0.24 g of NaF-TiO2 / rGO is ultrasonically dispersed in 40 mL of ethanol to obtain an ethanol suspension of NaF-TiO2 / rGO; then, 100 mL of ethanol is added to 1.2 mL of polyvinyl butyral, and the mixture is heated at 100° C. and stirred until dissolved, and then 0.4 g of polyurethane sponge is added and stirred evenly, and then the ethanol suspension of NaF-TiO2 / rGO is added, and after ultrasonic mixing, the mixture is dried in a blast drying oven at 80° C. until the liquid is completely evaporated, and then ultrasonically cleaned in distilled water to remove the NaF-TiO2 / rGO that is not firmly loaded on the surface of the polyurethane sponge; the mass of NaF-TiO2 / rGO is 60% of the mass of the polyurethane sponge.
[0084] Embodiment 15
[0085] The difference between this embodiment and embodiment 1 is that in step (3), 0.32 g of NaF-TiO2 / rGO is ultrasonically dispersed in 40 mL of ethanol to obtain an ethanol suspension of NaF-TiO2 / rGO; then, 100 mL of ethanol is added to 1.2 mL of polyvinyl butyral, and the mixture is heated at 100° C. and stirred until dissolved, and then 0.4 g of polyurethane sponge is added and stirred evenly, and then the ethanol suspension of NaF-TiO2 / rGO is added, and after ultrasonic mixing, the mixture is dried in a blast drying oven at 80° C. until the liquid is completely evaporated, and then ultrasonically cleaned in distilled water to remove the NaF-TiO2 / rGO that is not firmly loaded on the surface of the polyurethane sponge; the mass of NaF-TiO2 / rGO is 80% of the mass of the polyurethane sponge.
[0086] Application Examples
[0087] When the photocatalytic and biodegradation coupled catalytic material obtained in the above embodiment is used to treat ciprofloxacin wastewater, the activated sludge used is taken from the secondary sedimentation tank of a sewage treatment plant. The SV of the sludge during inoculation is 30The SVI is 92mL / g, the MLVSS / MLSS is about 49%, and the sludge concentration inoculated into each reactor is controlled at 1500mg / L. The experimental water is artificially prepared simulated urban sewage, and the specific components are as follows: C2H3NaO2·3H2O (250mg / L), NaHCO3 (110mg / L), CaCl2 (30mg / L), MgSO4·7H2O (40mg / L), NH4Cl (28mg / L), KH2PO4 (8mg / L).
[0088] The polyurethane sponge loaded with NaF-TiO2 / rGO obtained in the example was immersed in activated sludge for 24 h and then transferred to the SBR reactor for operation for 10 days. The experimental water in the SBR reactor was the artificially prepared simulated urban sewage. The aeration rate was controlled by a rotor flowmeter at 0.3 m / s. 3 / h speed to supply oxygen to the reactor so that the sponge carrier can be uniformly fluidized in the reactor, and the switch of the system is automatically controlled by a timer. The reactor is placed at room temperature and operates for two cycles a day. The specific mode is as follows: water inlet 10min, aerobic 240min, anoxic 180min, water outlet 10min, and the rest of the time is idle; on the 11th day, the obtained polyurethane sponge is taken out and placed in an SBR reactor without activated sludge for operation, and CIP is added step by step to the SBR reactor (0.1 mg / L for 11-25 days, 1.0 mg / L for 26-40 days, 10.0 mg / L for 41-55 days, and 20.0 mg / L for 56-70 days). The experimental water is artificially prepared simulated urban sewage to obtain an ICPB system that can tolerate antibiotics, and the degradation rate of CIP and the stability of ICPB are simultaneously detected; Example 1 The obtained ICPB biofilm is as follows Figure 1 As shown, it can be seen that after adding CIP to the ICPB system, the microorganisms on the carrier are still evenly and fully distributed inside the carrier.
[0089] Application Comparative Example 1
[0090] The difference between this comparative example and the above application examples is that a simple polyurethane sponge is immersed in activated sludge and exposed for 24 hours, and then transferred to the SBR reactor for operation for 10 days. The experimental water in the SBR reactor is the artificially prepared simulated urban sewage, and the aeration volume is controlled by a rotor flowmeter at 0.3m 3 / h speed to supply oxygen to the reactor so that the sponge carrier can be uniformly fluidized in the reactor, and the switch of the system is automatically controlled by a timer. The reactor is placed at room temperature and operates for two cycles a day. The specific mode is as follows: water inlet 10min, aerobic 240min, anoxic 180min, water outlet 10min, and the rest of the time is idle; on the 11th day, the obtained polyurethane sponge is taken out and placed in an SBR reactor without activated sludge for operation, and CIP is added step by step into the SBR reactor (0.1mg / L for 11-25 days, 1.0mg / L for 26-40 days, 10.0mg / L for 41-55 days, and 20.0mg / L for 56-70 days). The experimental water is artificially prepared simulated urban sewage, and a single biofilm is obtained, such as Figure 2 As shown, there are very few microorganisms on the carrier, and the degradation efficiency of antibiotics is bound to be reduced.
[0091] Application Comparative Example 2
[0092] The difference between this comparative example and the above application examples is that the polyurethane sponge loaded with NaF-TiO2 / rGO obtained in the example is immersed in activated sludge for 24 hours and then transferred to the SBR reactor for operation for 10 days. The experimental water in the SBR reactor is the artificially prepared simulated urban sewage. The aeration rate is controlled by a rotor flowmeter at 0.3m 3 / h rate to supply oxygen to the reactor so that the sponge carrier can be evenly fluidized in the reactor, and the switch of the system is automatically controlled by a timer. The reactor is placed at room temperature and runs two cycles a day. The specific mode is as follows: water inlet 10 minutes, aerobic 240 minutes, anoxic 180 minutes, water outlet 10 minutes, and the rest of the time is idle; on the 11th day, the obtained polyurethane sponge was taken out and placed in an SBR reactor without activated sludge. The experimental water was artificially prepared simulated urban sewage, without adding CIP, to obtain ICPB biofilm.
[0093] Figure 3 With the increase of graphene oxide content, the degradation of antibiotics by photocatalytic and biodegradable coupling catalytic materials first increased and then decreased. The appropriate content of rGO can convert the photogenerated electrons (e - ) quickly transfers, promoting its separation from the hole, and providing more active sites to promote the catalytic reaction. When more rGO is generated, some of it will cover the surface of NaF-TiO2, making the generated e - decrease, resulting in a slight decrease in the photocatalytic performance of the material;
[0094] Figure 4As the content of sodium fluoride increases, the degradation of antibiotics by the photocatalytic and biodegradable coupling catalytic material first increases and then decreases. Sodium fluoride can reduce the surface energy of the
[001] crystal plane and make the catalytic material have a stronger absorption capacity in the visible light region, ensuring good catalytic degradation efficiency. However, when the content of sodium fluoride increases, the crystal surface will be partially etched, resulting in a decrease in active sites, leading to a decrease in the photocatalytic activity of the catalytic material.
[0095] Figure 5 With the hydrothermal reaction temperature, the degradation of antibiotics by the photocatalytic and biodegradable coupling catalytic material first increases and then decreases. The initial increase in the hydrothermal reaction temperature can increase the collision opportunities between crystals, which is conducive to the replacement of the original oxygen-containing functional groups by NaF-TiO2 nanoparticles and the attachment to graphene to obtain a catalytic material with better catalytic degradation efficiency. However, when the hydrothermal reaction temperature increases, it will cause partial agglomeration of the grains to increase their particle size, reduce the specific surface area and interface energy, and thus affect the photocatalytic performance.
[0096] Figure 6 It can be seen that as the loading amount of photocatalytic and biodegradation coupled catalytic materials on the polyurethane sponge increases, the degradation rate of antibiotics also increases, reaching 96.3%;
[0097] Figure 7 It can be seen that when the CIP concentration in the wastewater is 0.1-20 mg / L, the CIP removal rate can reach more than 97.8% after 240 minutes of illumination.
[0098] The ICPB system obtained in Comparative Example 2 was directly used to treat CIP-containing wastewater. Due to the acute impact of CIP, a large amount of biofilm fell off, resulting in the inability of the photocatalytic degradation products of CIP to be quickly utilized by microorganisms, reducing the rate of pollutant degradation and mineralization.
[0099] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A photocatalytic and biodegradation coupled catalytic material, characterized in that: The invention comprises a polyurethane sponge and a sodium fluoride-based TiO2 / reduced graphene oxide composite material loaded on the polyurethane sponge. The polyurethane sponge and the sodium fluoride-based TiO2 / reduced graphene oxide composite material are connected by a thermoplastic resin adhesive.
2. The photocatalytic and biodegradable coupled catalytic material according to claim 1, characterized in that: The mass of the sodium fluoride-based TiO2 / reduced graphene oxide composite material is 20-80% of the mass of the polyurethane sponge.
3. The photocatalytic and biodegradable coupled catalytic material according to claim 1 or 2, characterized in that: The preparation method of a sodium fluoride-based TiO2 / reduced graphene oxide composite material comprises the following steps: dropping a sodium fluoride dispersion into a tetrabutyl titanate dispersion for mixed reaction; aging, drying and grinding the product, and then calcining at high temperature to obtain a TiO2 material; then adding the TiO2 material, graphene oxide and sodium fluoride into the mixed solution for hydrothermal reaction; and finally washing, drying and grinding.
4. The photocatalytic and biodegradable coupled catalytic material according to claim 3, characterized in that: The mass percentages of TiO2 material, graphene oxide and sodium fluoride are 35-90%, 0.1-0.5% and 10-65% respectively.
5. The photocatalytic and biodegradable coupled catalytic material according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 80-160°C and the time is 5-10 hours.
6. A method for preparing the photocatalytic and biodegradable coupled catalytic material as claimed in claim 1, characterized in that: Add an alcohol compound to a thermoplastic resin adhesive, heat and stir until dissolved, add a polyurethane sponge and stir evenly, then add a suspension of a sodium fluoride-based TiO2 / reduced graphene oxide composite material, mix evenly, and then dry and wash.
7. The preparation method according to claim 6, characterized in that: The mass of the polyurethane sponge relative to the alcohol compound is 0.1-1.0 g / 100 mL.
8. Use of the photocatalytic and biodegradation coupled catalytic material as claimed in claim 1 in treating ciprofloxacin wastewater.
9. The use according to claim 8, characterized in that: The photocatalytic and biodegradation coupling catalytic material is immersed in activated sludge for exposure, and then transferred to an SBR reactor for operation. The obtained photocatalytic and biodegradation coupling catalytic material is then taken out and placed in an SBR reactor without activated sludge for operation.
10. The use according to claim 9, characterized in that: When operating in an SBR reactor without activated sludge, ciprofloxacin was added stepwise to the experimental water.
Citation Information
Patent Citations
Preparation method of photocatalytic carrier with nano-scale inorganic catalyst powder combined with surface of organic high-molecular polymer
CN110975932A
Photocatalysis-biodegradation coupled wastewater treatment composite material and method for treating sulfamethoxazole-nitrate wastewater
CN117902727A
Cited By
Hydrothermal carbonized carbon photocatalysis and biodegradation direct coupling system as well as preparation method and application thereof
CN120774583A